Technical Perspective Back to the Edge. - Nikhil, Rishiyur S. (Communications of the ACM, 2019)
The article discusses the possible use of dataflow for computation circuits to best exploit parallelism for performance. Topics include the evolution of dataflow computing methods, the efficient management of data flow between circuits by von Neumann central processing units (CPUs), and the use of explicit dataflow graph execution (EDGE) computing.